2010
DOI: 10.1002/art.27459
|View full text |Cite
|
Sign up to set email alerts
|

Does pregnancy provide vaccine‐like protection against rheumatoid arthritis?

Abstract: Objective. Previous studies have evaluated the correlation between rheumatoid arthritis (RA) risk and pregnancy history, with conflicting results. Fetal cells acquired during pregnancy provide a potential explanation for modulation of RA risk by pregnancy. The present study was undertaken to examine the effect of parity on RA risk.Methods. We examined parity and RA risk using results from a population-based prospective study in Seattle, Washington and the surrounding area and compared women who were recently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 28 publications
4
92
3
2
Order By: Relevance
“…In addition, the reduction in RA risk that is associated with increasing parity is only seen after the first year postpartum. 23 In conclusion, despite a higher number of FMc sources, no significant change in FMc was observed with increasing parity, and increasing parity was associated with a significantly lower concentration of MMc. These observations raise interesting questions about the interaction of acquired grafts within a host, including whether such interactions may ultimately lead to the emergence and persistence of 1 dominant source of Mc, as is seen in dual CBT and which may impact the endurance of the NIMA effect.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, the reduction in RA risk that is associated with increasing parity is only seen after the first year postpartum. 23 In conclusion, despite a higher number of FMc sources, no significant change in FMc was observed with increasing parity, and increasing parity was associated with a significantly lower concentration of MMc. These observations raise interesting questions about the interaction of acquired grafts within a host, including whether such interactions may ultimately lead to the emergence and persistence of 1 dominant source of Mc, as is seen in dual CBT and which may impact the endurance of the NIMA effect.…”
Section: Discussionmentioning
confidence: 71%
“…6 Interestingly, some disease states that have been found to vary according to a woman's reproductive history (primarily parity, or number of deliveries) also are associated with altered Mc. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Thus, there exist parallel associations between Mc and disease, and parity and disease. Given the concurrent associations, we sought to answer the question whether parity might alter Mc in such a way as to support the hypothesis of a functional connection between Mc and disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been reported that there is an increased risk of developing RA or an exacerbation of an already established RA particularly in the first 3–12 months after delivery [26]. Additionally, Guthrie et al [27] also found that a shorter time interval from the last childbirth is strongly and significantly correlated with a reduced RA risk.…”
Section: Introductionmentioning
confidence: 86%
“…A significant reduction in risk for the development of new RA is observed for parous compared with nulliparous women, and interestingly, this effect wanes with increasing time from the last birth. While the explanation for these observations is not known, a reasonable explanation is that there is an acquisition of HLA disparate fetal Mc carrying HLA alleles that are protective for RA [6]. However, the fetal Mc that a woman acquires could also carry HLA alleles associated with RA-risk.…”
Section: Autoimmune Diseasementioning
confidence: 97%